Sex differences in cytokines and adipokines in obese patients with PsA and controls undergoing a weight loss intervention - Ingrid Larsson; Björn Eliasson; Lennart Jacobsson; Annelie Bilberg; Mats Dehlin; Eva Klingberg; Inger Gjertsson; Anton Jonatan Landgren; Charlotte A Jonsson; Linda Torres (RMD Open, 2024)
Objective In this post hoc analysis of a previously published study, we compared cytokines and adipokine levels in women and men with psoriatic arthritis (PsA) at baseline (BL) and 6 months (M6) following a weight loss intervention.Methods Patients with PsA (n=41) between 25 and 75 years of age, with body mass index (BMI)≥33 kg/m2 were included in a weight loss intervention with a very low energy diet (VLED) for 12 or 16 weeks depending on BL BMI<40 or ≥40 kg/m2. As controls (n=39), obese individuals, already planned for VLED treatment were recruited and matched for sex, age and weight to the patients with PsA. Cytokines and adipokines were measured at BL and M6.Results At BL, serum levels of interleukin (IL)-23, leptin and high molecular weight-adiponectin were higher in women with PsA compared with men, whereas serum levels of interferon (IFN)-γ, IL-12/IL-23 p40 and IL-13 were significantly lower in women. Serum IL-23 was significantly reduced at M6 compared with BL in women but not in men with PsA. In women with PsA, the reduction in IL-23 at M6, ∆IL-23, were positively correlated with ∆Disease Activity Score 28 C reactive protein (CRP) (Spearman’s correlation (rS)=0.486, p=0.016), ∆CRP (rS=0.468, p=0.021), ∆leptin (rS=0.683, p<0.001) and negatively correlated with ∆total-adiponectin (rS=−0.433, p=0.035). Also in women, ∆Disease Activity in Psoriatic Arthritis was positively correlated with ∆tumour necrosis factor-α (rS=0.417, p=0.034), ∆IL-1β (rS=0.550, p=0.034), ∆IFN-γ (rS=0.414, p=0.035) and ∆leptin (rS=0.410, p=0.038). None of these correlations were significant in men with PsA.Conclusions Women and men with PsA differed with regard to serum levels of cytokines and adipokines before and after weight loss.